Wild elephants vary in their attraction to novelty across an anthropogenic landscape gradient - Sarah L. Jacobson; Sangpa Dittakul; Mananya Pla-ard; Supang Sittichok; Marnoch Yindee; Joshua M. Plotnik (Royal Society Open Science)
Research on how wild animals respond to novelty is becoming more relevant as the overlap between natural habitats and human-dominated landscapes increases. Wild Asian elephants spend more time in anthropogenic landscapes as their habitat is converted to agriculture. Greater neophilia and exploration may allow elephants to successfully access agricultural resources, which may cause negative interactions with people. We compared wild elephant reactions to novel objects in two different landscapes in Thailand (near agriculture and deep inside a protected sanctuary). We also assessed consistency in measures for individuals exposed to different objects to determine whether their reactions could be considered personality traits. Elephants tested near agriculture were more neophilic and exploratory than those inside the sanctuary. However, the limited sample of elephants exposed to both novel objects did not demonstrate consistency in their reactions, and thus we could not determine whether neophilia or exploration were personality traits in this population. Neophilic and exploratory elephants likely benefit from high-quality agricultural resources, but at a potential cost to both elephants and humans. Knowledge about the elephants’ behaviour and attraction to particular landscapes could aid in human–elephant conflict mitigation efforts that consider the needs of both species and aim for more stable coexistence.